Microplastic Identification of Tinfoil Barb (Puntius schawanafeldii) in Koto Panjang Dam Kampar Regency Riau Province - Lily Sherly Margaretha; Budijono Budijono; Muhammad Fauzi (Jurnal Perikanan dan Kelautan, 2022)
Plastic waste can be found everywhere, including in the Koto Panjang Dam. As the plastic waste degraded, the microplastic materials may be distributed in the water and it may be accidentally swallowed by omnivorous fishes such as Puntius schawanafeldii. To understand the presence of the microplastic materials in the fish stomach, a research has been conducted in December 2020 - February 2021. The number of P. schawanafeldii captured was 30 using fish net in 3-5 inch mesh size. The fish was dissected and the stomach was removed. Then the stomach content was added with 10% KOH and was incubated for 2 weeks to delute the organic materials. Then was investigated under a binocular microscope to find out the microplastic materials. Results shown the type of microplastic present in the stomach of P. schawanafeldii was namely film, fibre, and fragment. The most common type of microplastic found was film, followed by fragments and fibre. The abundance of microplastic in the stomach of P. schwanafeldii was around 2 – 15,8 particles/fish.